2011
DOI: 10.1007/s11738-011-0860-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of triadimefon: a triazole fungicide on oxidative stress defense system and eugenol content in Ocimum tenuiflorum L.

Abstract: The effect of triadimefon (TDM) a triazole compound on antioxidant potential and eugenol content was studied in Ocimum tenuiflorum L. The plant was subjected to 15 mg/l TDM by soil-drenching on 50th, 70th and 90th days after planting (DAP). Analyses were carried out on 60th, 80th and 100th DAP. Both enzymatic and nonenzymatic antioxidant potential estimation was carried out. The non-enzymatic antioxidant viz ascorbic acid, a-tocopherol and reduced glutathione were found to increase under triadimefon treatment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Extensive laboratory and epidemiological studies have suggested that GT and GT polyphenols, especially EGCG, have preventive effects against chronic diseases including heart disease, diabetes, neurodegenerative disease, and cancer (Frei and Higdon, 2003). Numerous mechanisms have been proposed to account for the cancer preventive effects of GT and EGCG in laboratory animal models (Cai et al, 2002; Imai et al, 1997; Kumar et al, 2012) The antioxidant activity of GT polyphenols and, more recently, the prooxidant effects of these compounds have also been suggested as potential mechanisms for cancer prevention (Divya Nair et al, 2012; Frei and Higdon, 2003; Lambert and Elias, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive laboratory and epidemiological studies have suggested that GT and GT polyphenols, especially EGCG, have preventive effects against chronic diseases including heart disease, diabetes, neurodegenerative disease, and cancer (Frei and Higdon, 2003). Numerous mechanisms have been proposed to account for the cancer preventive effects of GT and EGCG in laboratory animal models (Cai et al, 2002; Imai et al, 1997; Kumar et al, 2012) The antioxidant activity of GT polyphenols and, more recently, the prooxidant effects of these compounds have also been suggested as potential mechanisms for cancer prevention (Divya Nair et al, 2012; Frei and Higdon, 2003; Lambert and Elias, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that medicinal plants are a potential source of antioxidants and ROS scavenger molecules (Arora et al, 2005; Divya Nair et al, 2012; Hatcher et al, 2012). Previous studies indicated the antioxidative property of medical plants such as GT (Azam et al, 2004; Thiagarajan et al, 2001), Cinnamomum zeylanicum (Ranjbar et al, 2006a), and Echium amoenum Fisch & C.A (Ranjbar et al, 2006b) have shown both the trapping effect of ROS as well as the inhibitory effect of lipid peroxidation and induction of TAC (Negishi et al, 2004).…”
Section: Discussionmentioning
confidence: 99%